Information Overload as a Mediator in the Relationship Between Instagram’s Social Media Use Intensity and Social Media Fatigue in Emerging Adulthood - Muhammad Aulia Sabarky; Nugraha Arif Karyanta; Fadjri Kirana Anggarani (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2023)
The massive use of Instagram in Indonesia aligns with the high need for emerging adults to socialize and express themselves. This makes users face much information, making it vulnerable to causing social media fatigue. This study examines the role of the information overload variable as a mediator of the relationship between the intensity of social media use and social media fatigue in the emerging adult group. Respondents in this study were aged 18-25 years, including 145 men and 182 women. Data was collected using three scales: SONTUS Revised Version, Information Overload Scales, and the SMFS Scale, adapted into Indonesian. The collected data was tested using PROCESS Macro (Model 4) involving intermediary variables with the help of the SPSS Statistics 26.0 for Windows program. This study's results indicate a mediating effect of excess information in the relationship between the intensity of social media use and social media fatigue. Complete mediation occurs because the direct impact becomes insignificant when the extra information variable is added to the equation